KONSEP FILOSOFIS BHANCAK TAUN SEBAGAI RELASAI ANTARA MASYARAKAT DAYAK SUAID DENGAN DWATA - Irenius Bima Abdiono; Mathias Jebaru Adon (Yayasan Literasi Sains Indonesia, 2023)
This research focuses on exploring the philosophical concept of Bhancak Taun as a relationship between the Dayak Suiad community and Dwata. Each tribe has its own way of expressing its beliefs. This can be seen in the lives of the Dayak Suiad people who make Bhancak Taun a medium for establishing relationships with Dwata, the Ruler of the universe. Bhancak Taun is one of the rituals or traditional ceremonies of the Dayak Suaid community which is held every year. Bhancak Taun is a form of recognition by the Dayak Suiad community that Dwata's existence is real and influential in their lives. This research aims to explore the concept of Bhancak Taun as a relationship between the Dayak Suaid community and Dwata. The method used in this research is a qualitative method through literature study and interviews. This research found that Bhancak Taun has a deep philosophical concept. The philosophical concept is found in the expression of gratitude of the Suaid Dayak community to Dwata for all the gifts that have been given and a form of request from the Suaid Dayak community to avoid various disasters. Apart from being a traditional ceremony, Bhancak Taun is also a norm of life that regulates the Suaid Dayak community to maintain the balance of the universe. Therefore, the role of Bhancak Taun is very central to the life of the Suaid Dayak community. Bhancak Taun brings awareness, so that you always see the goodness of Dwata and a reminder to preserve the universe.